A novel piezoelectric structure for harvesting energy from water droplet: Theoretical and experimental studies. (1st October 2021) - Hao, Guannan; Dong, Xiangwei; Li, Zengliang
Abstract: Toward applications for supplying low-energy consumed devices like remote sensors, a novel structure of piezoelectric substrate is proposed by combining polyvinylidene fluoride beams with elastic film, which shows higher performance than typical cantilever and fixed-fixed structures in collecting energy from water droplet impact. To evaluate the performance, the electromechanical behaviors of substrate are studied by conducting droplet impact tests and also with the aid of the developed theoretical model. Results show that there exists an optimal design of parameters which can lead to higher peak voltage and energy collected than single cantilever beam. The predicted results also show that based on similarity principle, the beam surface can be greatly enlarged to collect more energy from the same impact momentum of water droplet so as to satisfy different scales of energy requirement. By making use of the great elasticity of film under fixed-fixed configuration, the tension in the film can be adjusted to adapt with various occasions of utilization that when the film is successively tightened, the peak voltage is gradually reduced while the vibration frequency is increased. Moreover, it is not sensitive to the impact location of water droplet as for the cantilever beam, which can indeed provide larger collecting area of water in practical utilizations. Overall, improvements have been made by the proposed structure in energy conversion efficiency, the scale of energy recovery and flexibility in applications. This work also lays a foundation for further practical utilizations of the proposed structure in a wide range of engineering fields such as the rain energy harvesting technology. Highlights: Novel piezoelectric structure by combing PVDF beams with elastic film. Development of electromechanical model in predicting dynamic response of substrate. Optimal design of substrate can lead to higher voltage output than cantilever beam. High Performance of the proposed structure in terms of efficiency and flexibility.